Caracterización de la producción y uso del lactosuero en las empresas lácteas (Campo Fino y Foodasa) de la parroquia San Miguel del cantón Salcedo provincia de Cotopaxi. - Lalaleo Tenelema, Thalia Tatiana (2021)
Whey is the liquid resulting from the coagulation of milk during cheese making. This is obtained after the separation of caseins and fat. Whey constitutes approximately 90% of the volume of the milk used in the production of cheeses and contains most of its water-soluble compounds. The present research work is aimed at characterizing the production and use of whey in the dairy companies (Campo Fino and Foodasa) of the San Miguel parish, Salcedo canton. In this way, the quality of whey derived from the production of fresh cheese was evaluated by means of physical-chemical and microbiological analyzes in an experimental way, where the whey samples were handled. After the results obtained, the descriptive method was used to establish a characterization regarding its composition and use of this milk residue in the production of fresh cheese. A waste management record was used to report the volume and uses of the whey discharged; also, the survey technique was applied to the production manager and the purchasers of the waste. According to the analyses carried out in the companies under study, the whey produced presents percentages in accordance with NTE INEN 2594:2011; for liquid whey, thus demonstrating that it is a sweet whey; due to its characteristics and protein content, it can be used in the production of products, generating alternatives to reduce the impact caused on the environment by this type of agroindustrial waste. This can also improve working conditions and obtain a change of scheme in the productive matrix.